Artifacts of personal safety in the subject space of students of the institute of higher education - Izabela B. Kotova; Tat'yana М. Krasnyanskaya; Valerii G. Tylets; Valeriya G. Veselova; Vladimir V. Iokhvidov (Rossijskij psihologičeskij žurnal., 2018)
The article deals with the study of the relation of students of institutes of higher education to the use of amulets, talismans, and charm as artifacts of safety. Artifacts of safety are material symbols the use of which involves improving the efficiency of self-safety. The considered artifacts entered into the system of subjective views of students; they believed in their effectiveness as means of defense and well-being of the person. The understanding of the purpose of amulets, talismans, and charms, established in the cultural space, formed the basis of this belief. This belief is rather a kind of social tradition; it presupposes own experience or magical orientation of the personality of the respondents only partially. Defense was the most attributive sphere of activity of the considered artifacts; they also could bring success and happiness. The study showed significant syncretism of students’ representations of the nature and functionality of the artifacts of safety. Their successful differentiation was based on the discrimination of origin and the nature of force. Despite the presence of the belief in the artifacts of safety, the overwhelming majority of the students were ready to use them in the present and especially in the future. The students explained the demand for the artifacts of safety in the future by the desire to ensure the protection of children. The authors distinguished and interpreted two groups of contradictions: (a) between the declared belief in the efficacy of the artifacts of safety and the subjects’ willingness to use them; (b) between the declared willingness to use the artifacts of safety and their actual use at the present time.